General principles of physical culture and sports and theoretical foundations - Ortiqov Umidjon Khudoyberdiyevich; Satimov Azamjon Ikromovich; Ortiqov Sirojiddin Xoldorjon o'g'li (Genius Publishing Group, 2022)
In this article, the general principles and theoretical foundations of physical culture and sports, the objective of personal upbringing and sports health activities, and a healthy lifestyle data provided.
Keywords: Physical education; sports; wellness; bodybuilding